Aging Heroes: Growing Old in Popular Culture - Jones, Norma; Batchelor, Bob (Rowman & Littlefield Publishers, 2015)
Despite the increasing number and variety of older characters appearing in film, television, comics, and other popular culture, much of the understanding of these figures has been limited to outdated stereotypes of aging. These include depictions of frailty, resistance to modern life, and mortality. More importantly, these stereotypes influence the daily lives of aging adults, as well as how younger generations perceive and interact with older individuals. In light of our graying population and the growing diversity of portrayals of older characters in popular culture, it is important to examine how we understand aging. In Aging Heroes: Growing Old in Popular Culture, Norma Jones and Bob Batchelor present a collection of essays that address the increasing presence of characters that simultaneously manifest and challenge the accepted stereotypes of aging. The contributors to this volume explore representations in television programs, comic books, theater, and other forms of media. The chapters include examinations of aging male and female actors who take on leading roles in such movies as Gran Torino, Grudge Match, Escape Plan, Space Cowboys, Taken,and The Big Lebowski as well as TheExpendables, Red,and X-Men franchises. Other chapters address perceptions of masculinity, sexuality, gender, and race as manifested by such cultural icons as Superman, Wonder Woman, Danny Trejo, Helen Mirren, Betty White, Liberace, and Tyler Perry’s Madea. With multi-disciplinary and accessible essays that encompass the expanding spectrum of aging and related stereotypes, this book offers a broader range of new ways to understand, perceive, and think about aging. Aging Heroes will be of interest to scholars of film, television, gender studies, women’s studies, sociology, aging studies, and media studies, as well as to general readers.